Academy’s stress and its consequences in body and emotional dimensions in university students - Ramírez Díaz, Jose Laurian (Rastros Rostros, 2021)
Stress is considered the epidemic of the 21st century and seems to be related to current lifestyles. The demands for professionalization mean that young people must professionalize at an early age, which creates academic stress. This document presents the results of a correlational study with university students. The analysis was carried out with the techniques of exploratory factor analysis, multivariate linear regression and ANOVA of factors, finding a relationship between academic stress and gender, and that the effects of the former increase when people limit their social coexistence due to training demands, being the most relevant consequences of academic stress are produced by its bodily effects, but by the high levels of anxiety that increases due to inattention when treating emotional symptoms at the same time, which wears out the person over time, manifesting severe physiological repercussions.
Keywords: Stress; Physiological effects; Health; College Student